PENINGKATAN KESADARAN GENERASI Z TERHADAP PERUBAHAN IKLIM DI INDONESIA - Liswandi; Iman Permana (Rural Development For Economic Resilience (RUDENCE), 2021)
ABSTRACT The activity was carried out in the form of a webinar and aimed to increase awareness of Generation Z regarding climate change, more specifically climate emergency activities and their handling by reducing carbon involving mangrove plants. The method used for this activity is the implementation using Zoom Meeting. The results of this webinar are proven by conducting a qualitative survey with the webinar participants via Google Form. The activity results showed that the participants of this webinar were satisfied with the existence of the webinar on climate change and mangroves because it opened the minds of the participants. However, there are also drawbacks to the webinars that have been carried out, namely the hosts are less interactive, and the question and answer session is too short. In addition, the participants also felt quite satisfied because the speaker explained the material very clearly, and there’s a game session   ABSTRAK Kegiatan ini dilakukan dalam bentuk webinar dan bertujuan untuk meningkatkan kesadaran generasi Z mengenai perubahan iklim, lebih spesifiknya adalah darurat kegiatan iklim serta penanganannya dengan cara mengurangi karbon yang melibatkan tanaman mangrove. Metode yang dilakukan untuk kegiatan ini adalah dengan menggunakan Zoom Meeting dan hasil dari webinar ini dibuktikan dengan melakukan survey secara kualitatif dengan para peserta webinar melalui Google Form. Hasil kegiatan menunjukkan bahwa para peserta webinar ini cukup puas dengan adanya webinar mengenai perubahan iklim dan mangrove karena membuka pikiran para peserta. para peserta juga merasa cukup puas karena pembicara menjelaskan materinya dengan sangat jelas ditambah dengan adanya sesi permainan